Review Pengembangan Formulasi Sediaan Nano Minyak Atsiri Terhadap Aktivitas Farmakologi - Aliya Azkia Zahra; Ike Susanti (Journal of Pharmaceutical and Sciences, 2023)
Essential oils are liquids from the extraction process of plants or parts of aromatic plants which generally contain volatile terpenoids. This oil is characterized by distinctive odor from each plant that causes by differences in its constituent compounds. Essential oils have many pharmacological activities such as antioxidant, antibacterial etc. The development of many nano formulations has been developed, including essential oils. Nanoemulsion, nanogel, and nanoemulgel are forms of nano formulations that are applied in the manufacture of pharmaceutical preparations containing essential oils. Therefore, the purpose of this review is to present the results of the latest research on essential oil formulations using nanotechnology that have been widely developed and their effect on pharmacological activity. The articles used in this review were published from 2013-2023 which are indexed by Scopus. The formulation of essential oil preparations in nano form enhances the pharmacological effects of essential oils including increasing the effects of antioxidants, antibacterial, antifungal, antiproliferative, antiviral and reducing toxicity which can be useful as a reference for nano preparation formulations for essential oils.